2018
DOI: 10.1371/journal.pone.0187028
|View full text |Cite
|
Sign up to set email alerts
|

The complex scenario of obesity, diabetes and hypertension in the area of influence of primary healthcare facilities in Mexico

Abstract: IntroductionAmong non-communicable chronic diseases (NCCD), diabetes and hypertension are the main cause of adult mortality worldwide. Among the members of the Organization for Economic Cooperation and Development, Mexico is first in prevalence of diabetes and second in obesity. To face this problematic situation of NCCDs the Ministry of Health declared a national epidemiological alert against the overweight, obesity and diabetes. The target of this study is to characterize the status of obesity, diabetes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…An observational study performed in Mexico showed that more than 70% of the adult population living in areas with high social marginality present with diabetes, hypertension, and obesity. 22 An analysis of different CV profiles and how the COVID-19 pandemic affected their care will help in developing support strategies to keep these patients within the healthcare system.…”
Section: Surveymentioning
confidence: 99%
“…An observational study performed in Mexico showed that more than 70% of the adult population living in areas with high social marginality present with diabetes, hypertension, and obesity. 22 An analysis of different CV profiles and how the COVID-19 pandemic affected their care will help in developing support strategies to keep these patients within the healthcare system.…”
Section: Surveymentioning
confidence: 99%
“…Mexico is currently the second most obese country and recent research predicts that in 2030, 39% of the population will be obese, affecting all economic groups, low-income and high-income populations. Obesity is comorbid with heart conditions, diabetes mellitus, hypertension, cancer or sleep apnea [ 6 , 7 ]. In 2016, the government of Mexico declared the epidemic of diabetes a national emergency and is seeking to improve the quality of care for some 13 million people with the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the government of Mexico declared the epidemic of diabetes a national emergency and is seeking to improve the quality of care for some 13 million people with the disease [ 8 ]. One estimate determines that the cost of managing diabetes in Mexico ranges from $700 to $3,200 a year, being the total annual expenditure of people with diabetes 6.027 billion dollars (78 billion pesos) [ 7 , 9 ]. Annually, ≈450 000 new cases of hypertension are diagnosed in Mexico and this number could double if it is considered that up to 47.3% of people with hypertension are unaware that they suffer from this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mexico has a particular situation. According to national self-reports and surveys, 65–72% of adult patients are overweight or obese [ 10 , 11 ]. On the other hand, the melanomas in our population differ from the melanomas that appear in the Caucasian population because there is a clear predominance of acral subtypes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%